Financial Management: text, problems and cases - Khan, M. H.; Jain, P. K. (New Delhi : Tata McGraw Hill Education, 2007)
Business
Keywords: Financial Management; Risk and Return; Portfolio; Valuation model; Financial analysis; Profit planning; Budgeting; Capital budgeting; Risk evaluation; Capital management; Inventory management; Capital financing; Capital structure; Bond and securitisation; Option valuation; Dividend policy; Corporate restructuring; Risk management; corporate governance